The influence of brand ambassador, country of origin, and brand credibility on purchase intention of Some By Mi products in Indonesia moderated by consumer ethnocentrism - Rozania, Via; Afifah, Nur; Listiana, Erna; Shalahuddin, Ahmad; Hasanudin, Hasanudin (Junal Ilmu Manajemen, 2024)
The entertainment industry is prevalent worldwide, one of which is Indonesia. This represents the existence of a wave of Korean culture or what is usually called the Korean Wave. Products from South Korea have become one of the attractions for fans of Korean culture in Indonesia in recent years due to the increasing popularity of the Korean Wave. One example is beauty products or cosmetics from South Korea. This research aims to determine the influence of brand ambassador, country of origin, and brand credibility on purchase intention for Some By Mi products in Indonesia moderated by consumer ethnocentrism. This research is a type of quantitative research. Data collection was carried out by distributing questionnaires to 210 respondents. The sampling technique in this research used nonprobability sampling with purposive sampling type. The analysis technique used in this research is structural equation modeling (SEM) using the AMOS 24 statistical tool. The research results show that brand ambassador, country of origin, and brand credibility positively and significantly affect purchase intention. Meanwhile, consumer ethnocentrism as a moderator negatively and significantly influences purchase intention. This research can contribute to business people responding to consumer preferences with diverse ethnocentric backgrounds.